An orbital hydatid cyst involving inferior rectus muscle: A case report. (3rd March 2016) - Saravi, Seyed Soheil Saeedi; Sabouni, Farah; Arefidoust, Alireza; Yaftian, Raheleh; Heydarzadeh, Sepideh; Rajabi, Mohammad Taher
ABSTRACT: The orbital hydatid cyst is a rare entity and although most of them are located in superolateral and superomedial angles of orbits, involvement of inferior sites is uncommon. We report a 12-year-old case of primary hydatid cyst situated in inferior rectus muscle which was undergone surgical removal. Magnetic resonance imaging (MRI) was used for differential diagnosis of hydatid cyst. Moreover, histological analysis was performed, after the cyst removal, to confirm the diagnosis. Early clinical and radiological evaluations and subsequent surgical excision is the mainstay of treatment and should be performed to prevent severe complications caused by the advanced and ruptured cysts. Abbreviations: MRI: magnetic resonance imaging; CNS: central nervous system; BCVA: best corrected visual acuity; CT: computed tomography; USG: ultrasonography